Psoriasis: an eye opener - a cross-sectional study in a Tertiary Care Hospital of South India - Hari Kishan Kumar Yadalla; Vivekananda; Kaushal Kumar; Megha Chandrashekar (Our Dermatology Online, 2015)
Introduction: Psoriasis is a multi-system chronic inflammatory skin disease targeting 2% to 3% of the general population. It is a prototype of immune dysregulation mediated by TH1 proinflammatory cytokines such as TNF-α, IFN-gamma, IL-6, and IL-12 with far reaching systemic effects. There is growing and emerging evidence that psoriasis patients have a higher prevalence of associated comorbid diseases, with severe skin disease portends a serious risk for development of these comorbidities and are found to have a higher association of extracutaneous disease manifestations. Aim: To look for eye involvement in psoriasis patients and to evaluate the risk and prognostic factors of disease association. Material and Methods: 200 Patients with psoriasis were screened for any eye involvement after few unusual case presentations with eye complications during the period from September 2013 - August 2014. Results: First case was a post cataract sudden loss of vision secondary to development of uveitis in a female patient aged 52 years, with past history of psoriasis with minimal skin lesions and no arthritis. Another 5 cases of psoriasis with eye involvement were detected during the screening employed in a series of 200 psoriasis cases. Conclusion: The present report highlights the importance of psoriasis and eye involvement, need for collaboration between dermatologists and ophthalmologists for thorough examination and evaluation prior to any surgical intervention and also further long term follow-up studies are warranted for confirmation of this causal relationship.